2020
DOI: 10.34172/ps.2020.43
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effects of Formulation of Channa micropeltes and Moringa oleifera through Anti-Inflammatory Cytokines Regulation in Type 1 Diabetic Mice

Abstract: Background: Diabetes mellitus type 1 (T1DM) is an autoimmune disease characterized by chronic inflammation of the β-pancreas cells. The immunomodulatory activities related to the role of anti-inflammatory cytokines might contribute to control the inflammatory response in T1DM. This study aimed to evaluate the immunomodulatory effect of Moringa oleifera-Channa micropeltes formulation (MC) based on the profile of CD4 + IL-4 + , CD4 + IL-10 + , and CD4 + TGF-β + in type 1 diabetic mice. Methods: A total of 30 mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…STZ had a structure similar to glucose that could enter the cell through GLUT2 (Graham et al, 2011). We selected strain BALB/c mice because this strain is a widely used animal model in diabetes mellitus research (Adharini et al, 2020). The liver regulates glucose level homeostasis through glycolysis, gluconeogenesis, and glycogen synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…STZ had a structure similar to glucose that could enter the cell through GLUT2 (Graham et al, 2011). We selected strain BALB/c mice because this strain is a widely used animal model in diabetes mellitus research (Adharini et al, 2020). The liver regulates glucose level homeostasis through glycolysis, gluconeogenesis, and glycogen synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…When the mice's blood glucose level exceeded 200 mg/dL, they were considered in T1DM condition. Previous experiment reported that T1DM in male mice BALB/c could be induced with a single high-dose injection of STZ (Adharini et al, 2020).…”
Section: Induction Of Diabetes Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes Mellitus (DM) is a metabolic disorder characterized by hyperglycemia an elevated blood glucose levels exceeding the normal range, 1 resulting from abnormalities in insulin secretion (due to dysfunction of β cells of islet), insulin resistance, or both. 2 This condition stems from either the inability of the pancreas to produce insulin or the body's inability to utilize insulin. 3 The International Diabetes Federation (IDF) reported in 2021 that the number of diagnosed diabetes patients worldwide is up to 537 million.…”
Section: Introductionmentioning
confidence: 99%